Drug Delivery System to Control Infectious Diseases - Shoji, Y.; Shimada, J.; Mizushima, Y. (Current Pharmaceutical Design, 2002)
Viral replication takes place only in the host cell. From this intrinsic characteristics of virus, therapeutics agents specifically target to the virus genome is quite difficult. However, genetic medicine toward viral gene is promising in terms of selective toxicity for viral infection. Genetic medicine including antisense DNA, ribozyme, aptamer, triplex and gene itself has been enthusiastically studied in the past decades. At the early age of genetic medicine research, there were many skepticisms about clinicla usage. However, the first antisense DNA is on the market in the USA and Europe. Although the mechanism of antisense manner is still controversial, it was clearly epoch-making in the human application of genetic medicine. Genetic medicine opens the possibility to combat virus replication in a sequence specific way.Virus utilizes the specific receptor on the host cells for entry this is the reason why virus has organ specificity (tropism). Since life cycle of each virus is unveiled, target for the therapeutic agent's reveals in a molecular level. Furthermore, decipher of viral genome has been carried out rapidly and inexpensively. Once we hand entire sequences of viral genome, more theoretical way to design genetic medicine targeted viral infection could be main stream in the development of antiviral agents. Furthermore, efficient drug delivery system (DDS) to deliver antiviral agents to the infectious site is highly needed. In this article, we will address the target molecule of antiviral agents and possible DDS for the infectious disease.
Keywords: genetic medicine